Раскройте скобки и упростите выражение 3(a- b) - 2(a+b) 4(x+ y) + 5(2x - y) 2,4 ( c - 3d)...

0 голосов
34 просмотров

Раскройте скобки и упростите выражение
3(a- b) - 2(a+b)
4(x+ y) + 5(2x - y)
2,4 ( c - 3d) - 1,3(2c- d)
- 3/4 (1/3m+ n ) - 1/4 (3m + n)
Помогите пожалуйста



Математика (109 баллов) | 34 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

3(a- b)  - 2(a+b)=3a-3b-2a-2b=a-5b
4(x+ y) + 5(2x - y)=4х+4y+10х-5y=14х-y
2,4 ( c - 3d) - 1,3(2c- d)=2.4c-7.2d-2.6c+1.3d=-0/2c-5/9d
- 3/4 (1/3m+ n ) - 1/4 (3m + n) =-1/4m-3/4n-3/4m-1\4n=-m-n=-(m+n)

(302k баллов)